Impact of Covid -19 on expanded program on Immunisation in District Dir lower Khyber Pakhtunkhwa - Abdullah; Salsbeel Khan; Iqra Hamid Khan; Tahira Ashraf (Journal of the Pakistan Medical Association, 2024)
Objectives: To study the impact of coronavirus disease-2019 on Expanded Program on Immunisation in a rural setting. Method: The descriptive, cross-sectional study was conducted in five union councils of District Dir Lower, in the Khyber Pakhtunkhwa province of Pakistan. Data was collected from March to August 2020, which was a period of lockdowns in the wake of the coronavirus disease-2019, and then from March to August 2021. The sample comprised children aged <2 years. Data was analysed using SPSS 25. Results: Of the 330 children, 210(63.6%) were boys, and 120(36.4%) were girls, and all 330(100%) were located in rural areas. First-phase data showed that the maximum coverage rate of immunisation was 258(78.2%) noted in OPV1(Oral Polio Vaccine) Penta1(Pentavalent vaccine), PCV10-1 (Pneumococcal pneumonia), and Rota 1(Rota Vaccine), and the least vaccination rate was 68.2% for Measle-1. In the second phase, 23% incline was noted in Measles-2 vaccination, followed by 16.3% in OPV2, Penta 2, PCV10-2 and Rota 2, 16% in Measles-1, 14% in OPV-3, Penta-3, PCV10-3, Rsota-3 and IPV, 11.5% in OPV-1, Penta-1, PCV10-1, and Rota-1, and 10.6% in OPV-0 and BCG-0. Conclusions: Immunisation programme was affected by lockdowns during the active phase of the coronavirus disease-2019 pandemic. Key Words: COVID-19, Immunisation, Coronavirus, Pandemic, Vaccination.